Compositional Programming and Testing of Dynamic Distributed Systems - Desai, Ankush; Phanishayee, Amar; Qadeer, Shaz; Seshia, Sanjit (ACM OOPSLA 2018, 2018)
A real-world distributed system is rarely implemented as a standalone monolithic system. Instead, it is composed of multiple independent interacting components that together ensure the desired system-level specification. One can scale systematic testing to large, industrial-scale implementations by decomposing the system-level testing problem into a collection of simpler component-level testing problems. This paper proposes techniques for compositional programming and testing of distributed systems with two central contributions: (1) We propose a module system based on the theory of compositional trace refjnement for dynamic systems consisting of asynchronously communicating state machines, where state machines can be dynamically created, and communication topology of the existing state machines can change at runtime; (2) We present ModP , a programming system that implements our module system to enable compositional reasoning (assume-guarantee) of distributed systems. We demonstrate the effjcacy of our framework by building two practical fault-tolerant distributed systems, a transaction-commit service and a replicated hash-table. ModP helps implement these systems modularly and validate them via compositional testing. We empirically demonstrate that the abstraction-based compositional reasoning approach helps amplify the coverage during testing and scale it to real-world distributed systems. The distributed services built using ModP achieve performance comparable to open-source equivalents.